What are clinically significant anti-drug antibodies and why is it important to identify them - Swanson, Steven James (Frontiers in Immunology, 2024)
The FDA has released new draft guidance to standardize how immunogenicity of protein therapeutics is described in product labels. A key aspect to this new guidance is that companies should describe anti-drug antibodies that have clinical significance in addition to reporting ADAs’ incidence. Factors to consider when determining clinical significance include if those antibodies have a significant effect on the drug’s pharmacokinetics, pharmacodynamics, efficacy, and/or safety. While in many instances, the humoral response to protein therapeutics does not have any clinical significance, there are cases where there is a clinically significant effect and it is important to communicate this information to physicians and patients. This new guidance also delineates where immunogenicity information should be listed in product labels which should provide consistency in how this information is listed. There are many factors that contribute to a therapeutic’s immunogenicity and determining clinical significance is both complex and challenging, requiring that companies perform thorough analyses with scientific rigor. The analysis that is now proposed to understand clinical significance of ADAs is a new concept and will require companies to develop a strategy for compliance. This manuscript sets forth some of the key considerations in answering this important question. One of the benefits that this new guidance will provide is a common approach for describing the immune response to therapeutics that will be located in a dedicated section of the label, providing valuable consistency across protein therapeutics. Section 12.6 in the Clinical Pharmacology portion of the label will contain the relevant immunogenicity information, which will make it much simpler to find immunogenicity information in product labels. This new guidance is currently being utilized for new protein therapeutics and companies are being requested to systematically revise the labels of previously approved drugs for compliance, although an absolute timeline for this has not been established as of this writing.